Examination of the needs of hygienizational patients of periodontological guidelines in Lublin - Baranowski, Mateusz; Wójcicka, Agnieszka; Czerniakiewicz, Kacper; Wysokińska-Miszczuk, Joanna (Journal of Education, Health and Sport, 2020)
Introduction: The dental treatment of every patient, who comes to the dental office, should start with his hygienization. The basis of treatment should be daily, careful oral hygiene at home. Clinical observations suggest that patients neglect or perform this incorrectly. Purpose of work: The aim of the study was to assess the oral hygiene condition of patients reporting to the periodontics clinic Materials and Methods: The medical documentation of 52 patients who came to the Clinic of Periodontology at the Clinical Center of the Medical University in Lublin in 2015-2016 was analyzed. There were 24 men and 28 women between 19 and 75 years of age. Extraoral and intraoral examination were performed and general medical history was taken. The CPITN index was used to assess the presence of dental deposits and tartar. Results: In the group of respondents; 47 patients [90.38%] required professional hygienization. Conclusions: Although almost all patients declare meticulous removal of dental deposits at least twice a day, more than 90% have shown numerous abnormalities in brushing or irregular oral hygiene. Patients do not have the skills or neglect to maintain oral hygiene, while being convinced about compliance with the hygiene regime. The doctor's role is to create conditions for education and patient motivation